Pengaruh Overconfidence dan Herding terhadap Keputusan Investasi Cryptocurrency yang Dimediasi oleh Persepsi Risiko - Komang Sri Widiantari; Waisnawa, I Kadek Dody Aditya; Suidarma, I Made; Ariwangsa, I Gusti Ngurah Oka (Universitas Muhammadiyah Pontianak, 2026)
This study examines irrational investor behavior in cryptocurrency investment decision-making. A quantitative approach was employed using questionnaire data collected through a Likert scale. The results show that overconfidence and herding have a positive and significant effect on both investment decisions and risk perception. Furthermore, risk perception significantly mediates the relationship between overconfidence and investment decisions. However, it does not significantly mediate the relationship between herding behavior and investment decisions. This study contributes to a better understanding of investor behavior and offers a new perspective on investment decision-making. The research was conducted in Bali with 200 cryptocurrency investors as respondents.